Effects of Deep Cryogenic Treatment on Wear Mechanisms and Microthermal Expansion for the Material of Drive Elements - Yuh-Ping Chang; Gino Wang; Jeng-Haur Horng; Li-Ming Chu; Yih-Chyun Hwang (Advances in Materials Science and Engineering)
By the composite heat treatments, the strength and the surface hardness of the materials of drive elements can be improved. Moreover, the high accurate and capable machines can be obtained. For the numerous composite heat treatments, the deep cryogenic treatment has been used widely for the purpose of low thermal expansion in the industry. Therefore, this paper is further to investigate the low friction, wear resistance, and low thermal expansion for the carburizing steels of drive elements with deep cryogenic treatment. According to the experimental results, martensitic transformation occurred after the deep cryogenic treatment. The effects of deep cryogenic treatment on wear mechanisms are significant. The shape of wear particles changes from slip tongue to smooth stratification. Moreover, the surface magnetization is smaller for the case of Carburizing-Deep cryogenic treatment. Hence, the wear mechanism becomes simple. Besides, the thermal expansion is significantly smaller for the case of Carburizing-Deep cryogenic treatment.